Efektivitas Mediasi dalam Penyelesaian Perkara Perceraian di Pengadilan Agama Garut Kelas IA - Muhammad Hibban Muttaqin (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Mediation is a dispute resolution process through negotiation or consensus for the parties assisted by a mediator and does not have the authority to decide or enforce the final decision of the case. In reality, the implementation process of mediation has been effective and in accordance with Supreme Court Regulation No. 1 of 2016 in resolving divorce cases, as evidenced by the number of successful cases resolved through mediation. The problems that will be discussed in this study are about the effectiveness of mediation and various inhibiting and supporting factors for the success of its implementation process, as a means of resolving cases, with the main objective of reducing the number of cases, and also to determine the extent of the success rate of mediation in divorce cases that occur in the Garut Religious Court. This type of research is field research with a juridical-normative approach. While the data analysis method used is descriptive analytical. In the data collection method, the author uses observation, interview and documentation methods. Based on the results of the study, it is known that mediation in the Garut Religious Court is effective, with a success rate of 7 cases out of 299 or 2.3%. In 2021, the Garut Religious Court recorded that it received 6,784 lawsuits, 1,095 divorce cases, and 4,648 lawsuits. There were 299 cases that went through the mediation stage, and 7 cases out of 299 or 2.3% of 2021 were successfully mediated.